Cardiorespiratory responses to the 30-15 intermittent ice test - Besson, C.; Buchheit, M.; Praz, M.; Dériaz, O.; Millet, G. (International Journal of Sports Physiology and Performance, 2013)
Purpose: In this study, the authors compared the cardiorespiratory responses between the 30-15 Intermittent Ice Test (30-15IIT) and the 30-15 Intermittent Fitness Test (30-15IFT) in semiprofessional hockey players. Methods: Ten players (age 24 ± 6 y) from a Swiss League B team performed the 30-15IIT and 30-15IFT in random order (13 ± 4 d between trials). Cardiorespiratory variables were measured with a portable gas analyzer. Ventilatory threshold (VT), respiratory-compensation point (RCP), and maximal speeds were measured for both tests. Peak blood lactate ([Lapeak]) was measured at 1 min postexercise. Results: Compared with 30-15IFT, 30-15IIT peak heart rate (HRpeak; mean ± SD 185 ± 7 vs 189 ± 10 beats/min, P = .02) and peak oxygen consumption (VO2peak; 60 ± 7 vs 62.7 ± 4 mL/min/kg, P = .02) were lower, whereas [Lapeak] was higher (10.9 ± 1 vs 8.6 ± 2 mmol/L, P < .01) for the 30-15IIT. VT and RCP values during the 30-15IIT and 30-15IFT were similar for %HRpeak (76.3% ± 5% vs 75.5% ± 3%, P = .53, and 90.6% ± 3% vs. 89.8% ± 3%, P = .45) and % VO2peak (62.3% ± 5% vs 64.2% ± 6%, P = .46, and 85.9% ± 5% vs 84.0% ± 7%, P = .33). VO2peak (r = .93, P < .001), HRpeak (r = .86, P = .001), and final velocities (r = .69, P = .029) were all largely to almost perfectly correlated. Conclusions: Despite slightly lower maximal cardiorespiratory responses than in the field-running version of the test, the on-ice 30-15IIT is of practical interest since it is a specific maximal test with a higher anaerobic component.